EVALUASI TAHAP AWAL HASIL PERAKITAN PADI HIBRIDA MELALUI PERCOBAAN DENGAN RANCANGAN AUGMENTED - Kartina, Nita; ., Satoto; Widyastuti, Yuni (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2021)
In the early plant breeding experiments usually are not possible to use an appropriate experimental design. The number of large genetic materials and seeds is limited so environmental heterogeneity cannot be controlled. The augmented design could be used to do this approach. The research aims were to study the use of augmented design and evaluate the yield and its yield component of hybrid rice genotypes and check varieties, in the early evaluation. The research was conducted in the second season of 2015 (October 2015 to March 2016) in Sukamandi Experimental Station of Indonesia Center for Rice Research (ICRR), Subang, West Java Province. The experiment used 455 hybrid rice genotypes and four checks varieties, namely Hipa 8, Hipa Jatim 2, Inpari 31, and Ciherang. Based on the statistic analysis, the yield of hybrid rice ranges from 9.09 t/ha (GMJ13/CRS1268) to 10.77 t/ha (GMJ13/CRS1284), with heterosis to yields of 5.83% to 44.95%. Some hybrid rice genotypes showed better agronomic traits than check varieties. The augmented design allows for the interpretation of statistically valid data. Character data obtained are corrected data (adjusted), which have been adjusted to check varieties.